The death of Kaakutja: a case of peri-mortem weapon trauma in an Aboriginal man from north-western New South Wales, Australia. (15th September 2016) - Westaway, Michael; Williams, Douglas; Wright, Richard; Wood, Rachel; Olley, Jon; Swift, Jaime; Martin, Sarah; Kemp, Justine; Rolton, Shane; Bates, William
Abstract: Abstract : Skeletal remains from a burial in New South Wales exhibit evidence of fatal trauma, of a kind normally indicative of sharp metal weapons, yet the burial dates to the mid thirteenth century—600 years before European settlers reached the area. Could sharp-edged wooden weapons from traditional Aboriginal culture inflict injuries similar to those resulting from later, metal blades? Analysis indicates that the wooden weapons known as 'Lil-lils ' and the fighting boomerangs ('Wonna ') both have blades that could fit within the dimensions of the major trauma and are capable of having caused the fatal wounds.